'Pragmatic complexity' a new foundation for moving beyond 'evidence-based policy making'?. (4th March 2017) - Ansell, Christopher; Geyer, Robert
ABSTRACT: Despite a range of criticism, the realm of policy still remains dominated by the rational, positivist and quantitative approaches of New Public Management, 'evidence-based' approaches and target/accountancy oriented 'scientific' management. Two notable attempts to develop an alternative to this dominant framework, however, have come from the older tradition of American pragmatism and the newer approach of complexity. In this article we introduce some of the core concepts of pragmatist philosophy and complexity relating to policy making. We then explore some of the key premises for bringing these two fields together and subsequently apply this 'pragmatic complexity' approach and a Stacey Diagram to drug policy. We argue that a marriage of pragmatism and complexity can provide a positive alternative conception of the relationship between scientific knowledge and decision-making and offers a way to integrate a scientific approach with democratic deliberation and values.